2021
DOI: 10.33462/jotaf.741367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical and Organic Fertilizer Treatments on Yield and Quality Traits of Industrial Tomato

Abstract: Increasing plant production by protecting the environment is one of the main goals of today's agriculture. On the other hand, the use of both inorganic and organic fertilizers is becoming increasingly extensive. This study was carried out in field conditions to determine the effects of organic and inorganic fertilization on yield and quality characteristics of industrial tomato (Solanum lycopersicum L., cv. Heinz 1015 F1). For this purpose, contents of fruit total soluble solid contents, total dry matter, titr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This is because organic fertilizers and inorganic fertilizers have their respective advantages. Inorganic fertilizers are the fastest way to maintain plant productivity because the nutrient elements provided are in the form of readily available ions (Turhan & Özmen, 2021). However, the use of organic fertilizers also has drawbacks.…”
Section: Resultsmentioning
confidence: 99%
“…This is because organic fertilizers and inorganic fertilizers have their respective advantages. Inorganic fertilizers are the fastest way to maintain plant productivity because the nutrient elements provided are in the form of readily available ions (Turhan & Özmen, 2021). However, the use of organic fertilizers also has drawbacks.…”
Section: Resultsmentioning
confidence: 99%
“…Cell membranes and the apoplast are also considerably affected (Geilfus, 2018;Hasanuzzaman & Fujita, 2022). Turhan and Özmen (2021) demonstrated that excessive chlorine caused a decrease in the total soluble solid content in pepper plants.…”
Section: The Drawbacks Of Chlorine-based Fertilizers To Plantsmentioning
confidence: 99%
“…Plant pests and diseases, in general, cause considerable crop losses, encouraging the use of pesticides to boost farm output. One of the primary goals of modern agriculture is to increase plant production while safeguarding the environment [ 2 ]. Pesticides, on the other hand, are xenobiotics; their frequent use during production leaves pesticide residues in crops after harvest; as a result, it is critical to effectively focus on monitoring and regulating their use from public health and environmental sustainability perspectives [ 3 ].…”
Section: Introductionmentioning
confidence: 99%